Improving Student Learning Outcomes in Science: A Culturally Responsive Approach Using Problem-Based Learning - Sofiya, Rizka; Hikmawati, Hikmawati; Zohriana, Zohriana (Journal of Science and Science Education, 2025)
This study aimed to improve student learning outcomes through the Problem-Based Learning (PBL) model combined with the Culturally Responsive Teaching (CRT) approach. The research focused on teaching the concept of metamorphosis in animals using the local folklore, "Tetuntel-tuntel dan Tegodek-godek," which involves frogs (complete metamorphosis) and monkeys (no metamorphosis). Conducted as a Classroom Action Research (CAR) in two cycles, the study involved 28 third-grade students at SD Negeri 29 Ampenan during the 2024/2025 academic year. Instruments used included pre-tests, post-tests, observation sheets, and interview guidelines to measure learning outcomes and engagement. The minimum competency criterion (KKM) was set at 75. The results revealed significant improvements in learning outcomes: the average test score increased from 70.00 in the first cycle, where 67.86% of students achieved mastery, to 81.00 in the second cycle, with 96.43% of students meeting or exceeding the KKM. The integration of PBL and CRT created an engaging and culturally relevant learning environment, which enhanced students' comprehension of metamorphosis while fostering cultural appreciation. This study highlights the effectiveness of combining culturally enriched materials with active learning strategies in science education to improve academic performance and student engagement